ENVIRONMENTAL RESOURCES CLIMATE CHANGE: AN EXPOSITION OF HERDSMEN TERRORISM IN TIVLAND OF BENUE STATE - GABRIEL T. TYUNGU; PETER MEMGA KERTYO (International Studies Journal)
This paper is an attempt to examine the scramble for environmental resources as a precipitating factor in the rise in herdsmen activities in Nigeria. The paper is informed by the fact that since the beginning of the 21st century, there has been an astronomic increase in the number of herdsmenactivitiesthat have resultantly led to the destruction of lives and properties. Scholars have identified a lot of factors that must inform the wanton destruction of villages and communities by maundering herdsmen in Nigeria. Although, environment factors are interrogated as exacerbating agents, literature on the nexus between the scramble for environmental resources, climate change and the seasonal changes that have characterized the activities of herdsmen have remained feeble. Thus, the work is aimed at contributing to the existing literature on the impact of environmental factors on conflicts in Tivland of central Nigeria. Using both qualitative and quantitative sources of historical data, the paper establishes that the struggle for environment resources coupled with climate change have informed the unwarranted killing, maiming and ransacking of Tiv communities by herdsmen. This, the paper argues, is eminent in the changes in the occurrence of these conflicts. Before now, clashes between herders and farmers was witnessed between the periods of December to March, owing largely to changes in environments in the Sahel region.  However, with the continuous environmental changes that are evident with desert encroachment and silting of the lake chad basin, the demography of the conflicts has changed to an all year around conflict. To mitigate these conflicts, the paper advocates for environmental campaigns on the impact of environmental factors on Herders-Farmers conflicts and calls on religious leaders to dissuade the minds of their adherents about the religious motives of the conflicts. This will ultimately erase the fear of cultural imperialism that have constituted as a knock in the wheel of efforts in addressing the herdsmen malady.